'Des singes, c'était le narcisse': class, imitation and performing monkeys in late-eighteenth century Paris. Issue 2 (4th May 2018) - Ramos-Gay, Ignacio
Abstract: This paper focuses on the use of performing monkeys in boulevard and foire theatres in late eighteenth-century Paris. I will concentrate on the issues raised by 'Turco, ' Jean-Baptiste Nicolet's legendary acting monkey at the Théâtre de la Gaîté, who was most cherished for his antics and ability to emulate the Comédie-Française's leading actor François-René Molé in 1767–1768. Relying on first-hand materials drawn from Nicolet's contemporaries' letters, drawings, 'anecdotes' and memoirs, I will contend that Turco's acrobatic feats anthropomorphized him to the extent of equaling modern circus acrobats. Secondly, I will argue that his success when parodying the 'sacred' French actor unearths class struggles reflected in the schism between the aristocratic, state-subsidized Comédie-Française and the rest of popular playhouses. I will conclude by stating that Turco's performances transcended Denis Diderot's acting theories swinging between intuitive and reflexive acting, as described in Paradox of the Actor (1773–1777).